'Nothing about us, without us' – A user/survivor perspective of global mental health. (October 2014) - Trivedi, Premila
Abstract Surprisingly little has been published directly from user/survivors in the burgeoning (and sometimes contentious) field of global mental health (GMH). This is important both ethically and practically if GMH is to benefit from the experiential expertise that user/survivors can bring, especially when they come from those lower or middle income countries (LMICs) where GMH programmes are targeted. Whether user/survivors from higher income countries (HICs) (whose experiential expertise has usually been developed in cultural/social/health/ economic/political contexts which are very different to those in LMICs) could also provide useful input to GMH is less clear. In this article I consider this directly from my perspective as a user/survivor in a HIC. I discuss how, in spite of contextual differences, there appear to be striking resonances between GMH in LMICs and mental health in HICs, particularly areas of concerns, e.g. diagnosis, treatment and cultural difference. I illustrate this using aspects of my own personal experience in a reflexive narrative way, and suggest that such narrative-illustrations could provide useful input in GMH. I also touch on other ways in which HIC user/survivors might become involved in GMH. I conclude by stressing that, however HIC user/survivors become involved in GMH, they must do so ethically, ensuring that those in LMICs always remain at the forefront.